Muscle-Derived Cells for Treatment of Iatrogenic Sphincter Damage and Urinary Incontinence in Men. (31st July 2012) - Gerullis, H.; Eimer, C.; Georgas, E.; Homburger, M.; El-Baz, A. G.; Wishahi, M.; Borós, M.; Ecke, T. H.; Otto, T.
Abstract : Introduction . Aim of this study was to assess the safety and efficacy of injection of autologous muscle-derived cells into the urinary sphincter for treatment of postprostatectomy urinary incontinence in men and to characterize the injected cells prior to transplantation. Methods . 222 male patients with stress urinary incontinence and sphincter damage after uroloical procedures were treated with transurethral injection of autologous muscle-derived cells. The transplanted cells were investigated after cultivation and prior to application by immunocytochemistry using different markers of myogenic differentiation. Feasibility and functionality assessment was achieved with a follow-up of at least 12 months. Results . Follow-up was at least 12 months. Of the 222 treated patients, 120 responded to therapy of whom 26 patients (12%) were continent, and 94 patients (42%) showed improvement. In 102 (46%) patients, the therapy was ineffective. Clinical improvement was observed on average 4.7 months after transplantation and continued in all improved patients. The cells injected into the sphincter were at least 50% of myogenic origin and representative for early stages of muscle cell differentiation. Conclusions . Transurethral injection of muscle-derived cells into the damaged urethral sphincter of male patients is a safe procedure. Transplanted cells represent different phases of myogenic differentiation.